Where do talents go in China: Factors at play in their city choice - Lian, Xinlei. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Shan Jiang.; Committee: Anna Hardman.; Keywords: Public policy, Economics, and Demography.; Compared with the rural-urban migration widely discussed in the literature, urban-urban migration has been a new trend in China, characterized by migrants' high education attainment. College graduates' migration decision, or their city location choice is important to municipalities to enhance local economic development. In this thesis, I conducted a discrete choice experiment by designing and disseminating a survey to study college graduates' individual city choice decision in Chinese cities. I find that recent graduates value short-term effects more than long-term effects when choosing a Chinese city after graduation. Monthly rents and monthly income are the most important factors among the studied variables (such as housing price, Hukou, and commute time, etc.); while housing price and hukou are deemed less important. City preferences also differ significantly by gender and education level. This thesis can be helpful for municipalities to adjust policies to attract talents to their cities.